The Correlation between Students’ Learning Styles and Learning Motivation on Their English Learning Achievement at SMP 2 Negeri Galesong Utara - Indah Triana Putri; Baso Jabu; Kisman Salija (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This research aims to determine the correlation between students' learning styles and learning motivation on English learning achievement of 8th grade students at SMP negeri 2 Galesong Utara. This research is a Quantitative descriptive method with Correlational research design. Technique sampling used in this research was Purposive Random Sampling.this research aims to answer 3 research question: (1) is there any correlation between students’ learning style and their English learning achievement? (2) Is there any correlation between students’ learning motivation and their English learning achievement? (3) Is there any correlation between students’ learning style and learning motivation on their English learning achievement?. The result showed that: (1) There was a significantly very weak negative correlation between students’ learning style and their English learning achievement with Pearson Correlation -0.139, (2) There was a very weak negative correlation but not significant between students’ learning motivation and their English learning achievement with Pearson Correlation -0.103, (3) There was no significant correlation between the students’ learning style and learning motivation on their English learning achievement with Sig. F Change 0.639. Based on these results, it can be concluded that learning styles and learning achievement are not the main determining factors in student learning achievement. This indicates that even though learning styles and learning motivation have an important role, there are other factors that are more dominant in influencing student learning achievement